Pelanggaran Batas Privasi Anak dalam Praktik Sharenting pada Kalangan Selebriti Indonesia - Genoveva Lidwina Sari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
The use of social media is increasingly massive, parents uploading photos, videos or other information about their children on social media has become increasingly common and has become a source of controversy in Indonesia recently. This research aims to investigate violations of children's privacy boundaries that occur due to sharenting practices among Indonesian celebrities. Using document study methodology, researchers compiled data related to sharenting practices that occurred in the latest Indonesian celebrity controversies and analyzed them in accordance with Communication Privacy Management (CPM) theory. The results of the research show that YouTube Adsense is a reward that is expected from parents who practice sharenting. Children are considered to have no awareness of their ownership of privacy so they are deemed unable to regulate their privacy rules. The failure to coordinate privacy boundaries between children and parents causes the boundaries of ownership of children's personal information to become blurred. The practice of sharenting by parents among Indonesian celebrities can raise ethical concerns regarding children's privacy rights and weak ownership of children's privacy in accordance with the concept in CPM theory.